Experimental study of sediment wash-off process over urban road and its dependence on particle size distribution - Yang Xiao; Bin Luan; Taotao Zhang; Dongfang Liang; Chi Zhang (Water Science and Technology, 2022)
Sediment originating from the urban road runoff is a main contributor to water pollution in urban areas. The size of the road sediment varies significantly, but its influence on sediment wash-off process has not been well investigated. In this study, sediments with different particle size distributions have been used in rainfall-runoff experiments over idealized urban road surface. The results show that, under the same experimental conditions, the capacity factor CF increases with the decrease of the median particle diameter D50, which is the dominant influencing factor on CF. The wash-off coefficient k is affected by both D50 and the grading of sediment. During the wash-off process, D50 of the sediment collected at the outlet increases with time. Such a grain coarsening phenomenon is particularly apparent when the road is originally covered with very fine sediments. Furthermore, the presence of coarse grains slows down the transport of fine sediment whose size is smaller than 14 μm. This shielding effect significantly affects the sediment wash-off process in the early stage of a rainfall event, while later on the interaction between particles of different sizes becomes unimportant. This study advances the understanding of sediment wash-off mechanism on urban road surface. HIGHLIGHTS Sediments with different particle size distributions have been used.; Experimental performance of sediment concentration, transport rate and particle size distribution.; The influence of particle size distribution on CF and k has been investigated.; The grain coarsening phenomenon is apparent when the road is originally covered with fine sediments.; The presence of coarse grains slows down the transport of fine sediment.;